KOMUNIKASI RITUAL DALAM UPACARA TAWUR LABUH GENTUH DI TAMAN MAYURA KOTA MATARAM - I Nyoman Buda Asmara Putra (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2021)
Communication is a fundamental need in human life. Bycommunicating, humans interact with God, fellow humans and the naturalenvironment to establish a harmonious life. Hindus in West Nusa Tenggaracarry out a tawur labuh gentuh ceremony at Mayura Park, Mataram Cityimplementing the tri hita karana concept. In the process of implementingthe tawur labuh gentuh ceremony, communication dynamics occur usingsymbols that need to be understood together. This study, entitled "RitualCommunication in the Tawur Labuh Gentuh Ceremony in Mayura Park,Mataram City", raises the issue, namely how is the form of ritualcommunication in the tawur labuh gentuh ceremony in Mayura Park,Mataram City? The general purpose of this research is to broaden scientificinsight about ritual communication and provide explanations to variousparties regarding the tawur labuh gentuh ceremony so that it can besocialized to the public and to religious institutions in making a policy. Itsspecific purpose is to describe and analyze the form of ritualcommunication in the tawur labuh gentuh ceremony in Mayura Park,Mataram City.This research was conducted using qualitative methods, so thatthe data analysis was carried out in a descriptive qualitative andinterpretative manner. Mayura Park, Mataram City, West Nusa TenggaraProvince was chosen as the research location because the tawur labuhgentuh ceremony was held in a large degree for the first time in this place.Besides that, the limited information makes Hindus not all know theprocession and the meaning of the ceremony from beginning to end, so itis deemed necessary to conduct research as a reference source. This formof ritual communication in the tawur labuh gentuh ceremony combinestwo theories used as a scalpel, namely Jurgen Habermas CommunicativeAction Theory and Charles Sander Pierce's Theory of CommunicationSemiotics.